ANALISIS MELODI SYAIR GENERASI PENERUS MUSIK IRINGAN LANGKAH JEPIN GERSIK PANTAI KOTA PONTIANAK - Nabilla Syafani; Agus Syahrani; Asfar Muniir (Universitas Tanjungpura, 2020)
AbstractThe Background of this research was to archieve the poem of Generasi Penerus Musik Iringan Langkah Jepin Gersik Pantai Kota Pontianak. The common problemsfound in this research were: How is the description of music in the Generasi Penerus poem. Then, the purpose of this research were: 1) Descriptions of vocal melodies in Generasi Penerus poem, 2) Descriptions of accompaniment music in Generasi Penerus poem. The method used in this research was descriptive qualitative method with a musicology approach. The data contained in this research were the result of direct observation and interviews with informants in the form of a violin, selodang, marwas, tambourine and poetry melody pattern. The data were analyzed qualitatively with data sources, namely Yusuf Dahyani, Anwar Djafar and Reza Zulianda, S.Pd who had played and active role and learned about the poem of Generasi Penerus Musik iringan Langkah Jepin Gersik Pantai Kota Pontianak. Keywords: Analysis, Generasi Penerus Poem, Langkah Gersik Pantai, Jepin, Kota Pontianak.